2017
DOI: 10.3136/fstr.23.637
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Development of a New Prebiotic Cereal-based Dairy Dessert: Rheological, Sensory and Physical Attributes

Abstract: This study aimed to develop a new prebiotic dairy dessert by adding different concentration of cereal flours (10 _ 16% w/w), inulin (6 and 8% w/w) and sugar (2 and 4% w/w) into dairy dessert formulation. A mixture design approach was used to create nine formulation of dessert samples. Desserts were evaluated by consumers who were asked to answer a check-all-that-apply (CATA) question. Water holding capacity (WHC) and syneresis values were also measured. Based on our results different concentration of flour, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Based on the results achieved by other researchers (Angelov et al, 2006;Ghanbari et al, 2017) a preliminary experiment was carried out on 3 different levels of raw cereal materials (oat and millet flour, each component 50% w/v): 7% w/v; 8% w/v and 10% w/v (Appendix, Figure A2). The selection criterion was to obtain the consistency of the product very similar to thick yogurt.…”
Section: Optimization Of the Fermented Cereal Dessert Recipementioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results achieved by other researchers (Angelov et al, 2006;Ghanbari et al, 2017) a preliminary experiment was carried out on 3 different levels of raw cereal materials (oat and millet flour, each component 50% w/v): 7% w/v; 8% w/v and 10% w/v (Appendix, Figure A2). The selection criterion was to obtain the consistency of the product very similar to thick yogurt.…”
Section: Optimization Of the Fermented Cereal Dessert Recipementioning
confidence: 99%
“…According to Canbulat and Ozcan (2015) short-chain and long-chain inulin in probiotic products revealed that short-chain inulin received higher scores for odour, taste, and overall acceptance than the samples with long-chain inulin. On the other hand, Ghanbari et al (2017) reported that producers should emphasize on the descriptors which negatively influence the hedonic dimension of cereal-based dairy desserts, Explanatory notes: Cereal-based desserts fermented with L. plantarum 021: 10-fresh, 17-after 7 days, 114-after 14 days, 121-after 21 days storage. Cereal-based desserts fermented with L. plantarum 021, with 1% w/v of inulin addition: 20-fresh, 27-after 7 days, 214-after 14 days, 221-after 21 days storage.…”
Section: Evaluation Of Sensory Qualitymentioning
confidence: 99%